Cardiac iodine-123 metaiodobenzylguanidine imaging predicts ventricular arrhythmia in heart failure patients receiving an implantable cardioverter-defibrillator for primary prevention. Issue 18 (17th August 2012) - Marshall, Andrew; Cheetham, Andrew; George, Robert S; Mason, Mark; Kelion, Andrew D
Abstract : Objective: To assess the prognostic value of cardiac iodine-123 metaiodobenzylguanidine ( 123 I-MIBG) scintigraphy to predict ventricular arrhythmias in patients with heart failure (HF) listed for implantable cardioverter-defibrillator (ICD) devices as primary prevention. Design, setting and patients: A prospective cohort study in 27 patients with HF referred for ICD implantation (alone or in combination with cardiac resynchronisation therapy) at a tertiary cardiac centre. Methods: Cardiac 123 I-MIBG scintigraphy was performed with calculation of early and late heart-to-mediastinum (H:M) ratios, washout rate, and summed defect score from single photon emission computed tomography (SPECT) acquisition. Resting myocardial perfusion SPECT using 99m Tc-tetrofosmin was also performed and a summed score calculated. Innervation-perfusion mismatch was evaluated by comparing SPECT scores. Main outcome measure: Ventricular arrhythmia requiring ICD therapy. Results: At 16 months median follow-up, 10 (37%) patients experienced a significant arrhythmic event. Compared with patients who suffered no event, these individuals had lower early and late H:M ratio and higher 123 I-MIBG SPECT defect scores: 1.83±0.43 versus 2.34±0.33 (p<0.001); 1.54±0.38 versus 1.96±0.38 (p=0.005); 37.0±9.4 versus 25.5±7.7 (p=0.001). Mismatch scores were also higher: 18.5±8.5 versus 8.4±5.0 (p<0.01). Optimal thresholds for predicting arrhythmia were <1.94 for early H:M ratio (sensitivity 70%, specificity 88%); <1.54 for late H:M ratio (sensitivity 60%, specificity 88%); 123 I-MIBG SPECT defect score ≥31 (sensitivity 78%, specificity 77%). Conclusions: In HF patients without prior ventricular arrhythmia, 123 I-MIBG imaging strongly predicts future arrhythmic risk. This may inform the process of case selection for ICD therapy on an individual basis, although no single measurement provides sufficient reassurance to obviate device implantation if otherwise clinically indicated.